SAT0055 Treatment Response To Conventional Disease Modifying Anti-Rheumatic Drugs (Dmards) and Biologics in Seropositive and Seronegative Patients with Early Rheumatoid Arthritis: Results from Catch (Canadian Early Arthritis Cohort). (15th July 2016) - Aberumand, B.; Bykerk, V.; Schieir, O.; Lin, D.; Boire, G.; Haraoui, B.; Hitchon, C.A.; Thorne, C.; Tin, D.; Keystone, E.C.; Jamal, S.; Pope, J.E.
Abstract : Background: Rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) status may affect treatment response in early rheumatoid arthritis (ERA). Objectives: To investigate differences in treatment response to disease modifying anti-rheumatic drugs (DMARDs) and biologics in ERA in seropositive versus seronegative patients for RF and/or ACPA. Methods: Data were obtained from The Canadian Early Arthritis Cohort (CATCH), a prospective multi-site study of patients with ERA who met 1987 or 2010 ACR/EULAR criteria for RA, had symptom duration <1 year, were not in remission at baseline and had RF or ACPA available, DAS28 scores at baseline and follow-up. Stratified multiple linear regression compared the effects of initial treatment with methotrexate (MTX) monotherapy, MTX combination therapy (defined as MTX plus one or more conventional DMARD), biologic therapy and other therapy on change in DAS28 (D DAS) at 3 and 6 month follow up in patients who were seropositive (RF + and/or ACPA+) and seronegative (RF- and ACPA-), patients who were RF positive and RF negative, and patients who were ACPA positive and ACPA negative, respectively. All multivariable models were adjusted for baseline age, gender, education, ethnicity, symptom duration, comorbidities, erosions and pain scores. Results: 1068 patients had a baseline mean (SD) age of 53.3 (15.0), symptom duration of 5.8 (3.0) months, DAS28 of 5.2 (1.3) and 74% were female. A total of 867 (81.2%) patients were seropositive and 201 (18.8%) were seronegative (RF positive 759 [66%], RF negative 385 [34%], ACPA positive 539 [61%], and ACPA negative 349 [39%]). Relative to the other therapy group, better treatment response to methotrexate combination therapy at 3 months was observed for patients who were RF+ (β: 0.45 [95% CI -0.74 to -0.17]) vs. RF- (β: 0.29 [95% CI -0.14 to 0.71]) and the combined seropositive (β: -0.29 [95% CI -0.56 to -0.02]) vs. seronegative group (β: -0.12 [95% CI -0.69 to 0.44) but not patients who were ACPA+ (β: -0.06 [95% CI -0.41 to 0.30]) vs. ACPA- (β: -0.41 [95% CI -0.84 to 0.02]), after adjusting for covariates. Similar results were observed when analyses were repeated with change in DAS at 6-months as the outcome as patients on methotrexate combination therapy who were RF+ (β: -0.47 [95% CI -0.81 to -0.13]) vs. RF- (β 0.15 [95% CI -0.39 to 0.71]) and those that were seropositive (β -0.32 [95% CI -0.65 to 0.00]) vs. seronegative (β: -0.20 [95% CI -0.97 to 0.56]) responded better to treatment. Response to other treatment strategies did not significantly differ by antibody in any grouping (Table ). Conclusions: In ERA, RF and ACPA status affected treatment response to MTX combination therapy, with better changes in DAS28 at 3 and 6-months in seropositive compared with seronegative patients. Given the complexity of rheumatoid arthritis management, the study findings potentially have implications for identifying prognostic indicators that may help inform therapeutic decision-making. Disclosure of Interest: None declared